ROLE OF INSULIN-LIKE GROWTH FACTOR-1 IN PATHOGENESIS OF CHRONIC ALCOHOLIC LIVER DISEASE IN RATS OF DIFFERENT AGE GROUPS - Рикало, Н.А.; Яровенко, Л.О. (World of Medicine and Biology, 2015)
During last ten years, chronic diffuse liver disease due to high morbidity and life-threatening consequences related to the actual problems of modern medicine. The actual topic is to study molecular mechanisms of reparative regeneration of pathological-altered liver and drugs influence on this process. The perspective is the studying of insulin-growth factor-1 (IGF-1) in rats of different age groups with chronic alcohol liver disease and under condition of pharmacocorrection using L-arginine-L-glutamate and quercetin, and study the correlation between IGF-1 and changes of biochemical markers of blood serum. Has been proved that chronic alcohol liver disease decreases the concentration of IGF-1 in the animals of all age groups, which correlates with biochemical markers of cytolysis and cholestasis syndromes. Established that under condition of pharmacocorrection using L-arginine-L-glutamate significantly increases the level of IGF-1, and available direct significant correlation with parameters of functional liver state, indicating restoration of liver parenchyma and its functional state by activation of reparative regeneration. Gained data shows that hepatoprotector L-arginine-L-glutamate has a potitive influence on the regenerative reparation process compared with quercetin.
Keywords: age features; chronic alcohol liver disease; insulin-like growth factor-1; biochemical parameters